Knowledge, attitudes, and practices toward zoonotic disease transmission among wildlife farmers in Vietnam - Ha Thi Thanh Nguyen; Lindahl, Johanna F.; Lam, Steven; Hung Nguyen-Viet; Sinh Dang-Xuan; Unger, Fred; Ling, J.; Lundkvist, Å.; Hu Suk Lee; Bett, Bernard K. (BioMed Central, 2025)
Background: Wildlife farming and trade in Southeast Asia contribute to the growing threat of zoonotic diseases. Despite the diversity of species farmed and the varying levels of risk they may pose, biosecurity practices among wildlife farmers remain underexplored. This study aimed to assess the knowledge, attitudes, and practices (KAP) of wildlife farmers in Vietnam to inform targeted interventions for zoonotic risk reduction.